Factors Affecting the Attraction of Visitors from the Agricultural Education Tour in the Tani Belimbing Group, Artha Mandiri, Tulungagung District, Indonesian Country - Romadi, Ugik; Yana, Hamyana; Yastutik, Yastutik; Rohman, Mochlisin Fatkur (Anuário do Instituto de Geociências, 2023)
Tourism is an important and most developed sector in the current era in supporting a country's economic growth. The tourism industry is currently able to produce products and services that are able to meet the needs of tourists so that tourists have a sense of satisfaction when they come to tourist sites. Tulungagung Regency has enormous potential related to tourist destinations. One of them is the Artha Mandiri Starfruit Farmers Group Agricultural Education Tour. Agricultural education tourism is a tour that prioritizes education or learning related to agriculture for tourist visitors. However, some aspects of educational tourism have not been able to maximize the potential to provide an optimal attraction for tourist visitors. This resulted in a very volatile related to the number of tourist visitors. The purpose of this study was to analyze the factors that influence the attractiveness of tourist visitors. The research method used is descriptive quantitative. Determination of the sample of respondents using proportionate stratified random sampling technique, and data analysis used is multiple linear regression. The results of this study indicate that 95% of visitors' attractiveness is in the high category. The factors that can affect the attractiveness of visitors at the location of agricultural education tourism in Tulungagung Regency are tourism material variables, accessibility, facilities and infrastructure, services, product quality and tourism concepts.